Implementasi Media Flashcard Dalam Mengenalkan Konsep Permulaan Matematika Pada Anak Usia Dini - Riadoh Riadoh; Mayana Futri; Risky Aulia; Kholidah Nur (Sekolah Tinggi Agama Islam Yayasan Pendidikan Ilmu Qur'an Baubau, 2025)
he ability of young children to understand beginning mathematics is still relatively low. This is because the learning process in early childhood is not carried out in accordance with the child's age development. The aim of this research is to describe the use of flashcard media in introducing early mathematics concepts to early childhood. The research method used in this research is using literature study techniques by reviewing several pieces of literature from various existing sources which are adapted to the research topic. The data analysis technique used in this research consists of three stages, namely data reduction, data presentation, and verification or drawing conclusions. The research results obtained in this study are that the use of flashcard media can help children understand initial mathematical concepts such as the concepts of numbers and geometry. This is because the flashcard media displays images, basic geometric shapes which have quantities corresponding to the number symbols 1-10, so that children can easily understand the meaning of the numbers 1-10 based on the quantity of the images of the basic geometric shapes displayed in the flashcard media.